2020
DOI: 10.1038/s41598-020-72240-y
|View full text |Cite
|
Sign up to set email alerts
|

Axial growth and refractive change in white European children and young adults: predictive factors for myopia

Abstract: This report describes development of spherical equivalent refraction (SER) and axial length (AL) in two population-based cohorts of white, European children. Predictive factors for myopic growth were explored. Participants were aged 6–7- (n = 390) and 12–13-years (n = 657) at baseline. SER and AL were assessed at baseline and 3, 6 and 9 years prospectively. Between 6 and 16 years: latent growth mixture modelling identified four SER classes (Persistent Emmetropes-PEMM, Persistent Moderate Hyperopes-PMHYP, Persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 40 publications
5
65
3
1
Order By: Relevance
“…The presence of +0.75 D or less of hyperopia at the age of 6 years indicates that myopia is likely to develop in the near future. 334,336,338 In prospective data from White European children, McCullough et al demonstrated that children presenting with a refractive error of <+0.63 D at 6-7 years and with at least one myopic parent were likely to develop myopia by age 13 years and those with no myopic parents were likely to develop myopia by 16 years. 338 Other work suggests that premyopes may also show specific binocular vision disorders.…”
Section: Management Of Premyopesmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of +0.75 D or less of hyperopia at the age of 6 years indicates that myopia is likely to develop in the near future. 334,336,338 In prospective data from White European children, McCullough et al demonstrated that children presenting with a refractive error of <+0.63 D at 6-7 years and with at least one myopic parent were likely to develop myopia by age 13 years and those with no myopic parents were likely to develop myopia by 16 years. 338 Other work suggests that premyopes may also show specific binocular vision disorders.…”
Section: Management Of Premyopesmentioning
confidence: 99%
“…334,336,338 In prospective data from White European children, McCullough et al demonstrated that children presenting with a refractive error of <+0.63 D at 6-7 years and with at least one myopic parent were likely to develop myopia by age 13 years and those with no myopic parents were likely to develop myopia by 16 years. 338 Other work suggests that premyopes may also show specific binocular vision disorders. 136 Since the visual profile of the myopic child is characterized by higher accommodative lag, 26,27 high AC/A ratio (esophoria at near) 135,139 and reduced accommodative flexibility, 26,27 it would be important to include tests that evaluate the binocular vision and not only refraction.…”
Section: Management Of Premyopesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the age at examination and definition of significant refractive error (hypermetropia, myopia, and astigmatism) differ between studies. Moreover, prior studies were not controlled for environmental factors and ethnic differences, which can affect refractive error 11 13 . Thus, the impact of syndromic and non-syndromic craniosynostosis on refractive error remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%